Cell Viability and Functionality of Probiotic Bacteria in Dairy Products - Vinderola, Gabriel; Binetti, Ana; Burns, Patricia; Reinheimer, Jorge (Frontiers in Microbiology, 2011)
Probiotic bacteria, according to the definition adopted by the World Health Organization in 2002, are live microorganisms, which when administered in adequate amounts confer a health benefit to the host. Recent studies show that the same probiotic strain produced and/or preserved under different storage conditions, may present different responses regarding their susceptibility to the adverse conditions of the gastrointestinal tract, its capacity to adhere to the intestinal epithelium, or its immunomodulating capacity, the functionality being affected without changes in cell viability. This could imply that the control of cell viability is not always enough to guarantee the functionality (probiotic capacity) of a strain. Therefore, a new challenge arises for food technologists and microbiologists when it comes to designing and monitoring probiotic food: to be able to monitor the functionality of a probiotic microorganism throughout all the stages the strain goes through from the moment it is produced and included in the food vehicle, until the moment of consumption. Conventional methodological tools or others still to be developed must be used. The application of cell membrane functionality markers, the use of tests of resistance to intestinal barriers, the study of surface properties and the application of in vivo models come together as complementary tools to assess the actual capacity of a probiotic organism in a specific food, to exert functional effects regardless of the number of viable cells present at the moment of consumption.